Difusi Inovasi dalam Film “Toilet” - Fransiska Fransiska (MUKASI: Jurnal Ilmu Komunikasi, 2024)
Sanitation is a polemic faced by developing countries. There are various reasons why sanitation is still underdeveloped in some areas such as poverty, culture, customs and others. Inability to sanitation can unknowingly result in losses for the community, losses experienced such as the emergence of diseases such as skin diseases, dirty environments and well water pollution. The purpose of this study is to illustrate that it is not easy to adopt a habit in society that is translated into an Indian film entitled "Toilet". The method used in this study is qualitative descriptive. The data collection technique uses observation by watching toilet films and determining the seconds that describe the spread of innovation absorption. The results of the study in this film illustrate that the absorption or adoption of a habit has a fairly difficult process. Where a country or region has norms that apply such as a culture that has been passed down from generation to generation, so if there is something new, it is not necessarily easily accepted by the surrounding environment. As depicted in the toilet film which explains that toilets, especially for defecating, are prohibited from being installed in the house, because ancestral teachings explain that dirty things should not be in the house, so that the activity is carried out in open fields or in fields.